Duration of Analgesic Free Period and Haemodynamic Stability Following Paediatric Herniotomy: A Comparison of Caudal Block Versus Pre-Incisional Field Block with Diclofenac Suppository - B, Kpalap P.; M, Usman Y.; A, Aliyu H.; R, Shaki; T, Malau K.; I, Nuhu S.; Y, Embu H.; S, Isamade E. (African Journal of Medicine, Surgery and Public Health Research, 2025)
Paediatric herniotomy, a common surgical procedure in children, demands effective perioperative pain management to ensure patient comfort and minimise complications. Optimal pain control is crucial in paediatric populations due to their heightened sensitivity to pain and the potential long-term impact of poorly managed acute pain on their neurodevelopment. The choice between caudal block and field block with diclofenac remains a subject of debate. Factors such as the duration of analgesic-free periods and haemodynamic stability need to be assessed to guide clinical decisions. This study was conducted in the Jos University Teaching Hospital, Jos, Nigeria, among paediatric patients presenting for inguinal herniotomy. We conducted a randomised, single-blind controlled clinical trial where patients were recruited through the purposive sampling technique. Inclusion criteria included elective day cases, open unilateral inguinal herniotomies, and children aged 1–6 years with ASA physical classes I and II. One group of patients received 1 mL/kg of 0.25% plain bupivacaine caudally, while the other group of patients received pre-incisional field block with 1 mL/kg of 0.25% plain bupivacaine and diclofenac suppository 1 mL/kg. duration of analgesic-free period and intraoperative haemodynamic parameters were assessed and documented. All the 58 enrolled patients were included in the final analysis, having completed the study. The study groups were comparable in all measured patient characteristics. The duration of analgesic free period was shorter in the caudal block group compared with the field block with diclofenac suppository group (282.86±18.43 minutes in the caudal block group and 291.03±16.33 minutes in the field block with diclofenac suppository group, p = 0.155). The heart rates, systolic blood pressures, diastolic blood pressures, and mean arterial pressures across both study groups were comparable from the start of surgery to the end of surgery. It can be concluded that both caudal block with 1 mL/kg of 0.25% plain bupivacaine and pre-incisional field block with 1 mL/kg of 0.25% plain bupivacaine plus 1 mL/kg of diclofenac suppository were comparable in providing effective post-herniotomy analgesia in the paediatric age group.